2020
DOI: 10.31883/pjfns/116590
|View full text |Cite
|
Sign up to set email alerts
|

Red Beetroot Juice Phytochemicals Bioaccessibility: an In Vitro Approach

Abstract: Beetroot, the cultivated form of Beta vulgaris subsp. vulgaris, is known for its various bene cial properties but more critical data about its bioactive compounds digestion is needed. In the present research, the bioaccessibility of phytochemicals in freshly prepared red beetroot juice was studied. Changes in total phenolics content, total avonoids content, contents of betacyanins and betaxanthins, phenolic acids pro le as well as the antioxidant activity were monitored before and after simulated gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 52 publications
4
26
0
1
Order By: Relevance
“…They are plant secondary metabolites with similar chemical properties, biological functions, and color spectrums as anthocyanins. However, anthocyanins and betalains never coexist together in plants [20]. Betalains are hydrophilic nitrogenous pigments, which could be subdivided into two main groups according to their chemical structure and color [26].…”
Section: Betalainsmentioning
confidence: 99%
See 3 more Smart Citations
“…They are plant secondary metabolites with similar chemical properties, biological functions, and color spectrums as anthocyanins. However, anthocyanins and betalains never coexist together in plants [20]. Betalains are hydrophilic nitrogenous pigments, which could be subdivided into two main groups according to their chemical structure and color [26].…”
Section: Betalainsmentioning
confidence: 99%
“…In the literature, there are discrepancies regarding the proportions between betacyanins and betaxanthins in beetroot, although it seems clear that the content of betacyanins in beetroot is much higher than that of betaxanthins. Some authors reported that the betacyanins represented about 80-90% of total betalains [28,29], while others found that the concentration of betacyanins was between 50-70% of total betalains [20,30]. The variation in these proportions determines the coloration of the root, and the higher content of betacyanins confers its typical red-purple pigmentation [3].…”
Section: Betalainsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the thermal stability of betalains present in by-products of red beetroot and their degradation along with raising temperature is manifested by the production of various betalain degradation products that have been determined in the work of Otálora et al ponins, being natural plant compounds exhibiting health benefi ts, in red beetroot for the fi rst time using high-speed counter-current chromatography in a new solvent system consisting of tert-butyl-methyl ether-butanol-acetonitrile-water. Aspects related to the fate of red beetroot phytochemicals after intake, such as the change in the total phenolics content, total fl avonoids content, contents of betacyanins and, betaxanthins, phenolic acids profi le as well as the antioxidant activity after simulated gastrointestinal digestion of red beetroot juice have been described by Desseva et al [2020]. Finally, the study of Płatosz et al [2020] shows the profi le of phenolic acids and fl avonoids of red beetroot and its fermentation product and explains whether the long-term consumption of fermented red beetroot juice affects phenolic compounds profi le in plasma and urine of volunteers.…”
Section: This Thematic Issue Of Polish Journal Of Food and Nutritionmentioning
confidence: 99%